2006
DOI: 10.4103/0250-474x.22969
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of controlled onset extended release multiparticulate systems for chronotherapeutic delivery of ketoprofen

Abstract: An oral controlled onset extended release dosage form intended to approximate the chronobiology of rheumatoid arthritis is proposed for site-specific release to the colon. The multiparticulate system consisting of drug-loaded cellulose acetate cores encapsulated within Eudragit S-100 microcapsules was designed for chronotherapeutic delivery of ketoprofen. Drug-loaded cellulose acetate cores were prepared by emulsion solvent evaporation technique in an oily phase at different drug:polymer ratios (1:1, 2:1 and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
3
5
0
Order By: Relevance
“…The same peaks were present in the diffractograms PM and SD but with low intensities, indicating the conversion of crystalline form of pure Ketoprofen to amorphous form in presence of PM and SDs. Moreover, the peak intensity of Ketoprofen was much more reduced as compared to pure Ketoprofen and PM, as shown in Figure 3b-c. Our results con irm the indings of other researchers [17][18][19][20]. …”
Section: X-ray Diffractometry Studiessupporting
confidence: 82%
See 2 more Smart Citations
“…The same peaks were present in the diffractograms PM and SD but with low intensities, indicating the conversion of crystalline form of pure Ketoprofen to amorphous form in presence of PM and SDs. Moreover, the peak intensity of Ketoprofen was much more reduced as compared to pure Ketoprofen and PM, as shown in Figure 3b-c. Our results con irm the indings of other researchers [17][18][19][20]. …”
Section: X-ray Diffractometry Studiessupporting
confidence: 82%
“…The SEM analysis showed that relatively smaller polyhedral crystalline forms of Glucosamine and Ketoprofen are clearly visible in PM, as shown in Figure 4c, the Ketoprofen has smallest, irregular, circular and plate like crystals in SDs, which are responsible for enhanced dissolution rate. Similar studies were conducted [17,20]. Our results con irm their indings.…”
Section: Scanning Electron Microscope Analysissupporting
confidence: 81%
See 1 more Smart Citation
“…All batches were prepared in triplicate. This method was developed on the basis of practical observations, which are discussed in the later part by carrying out certain modifications to the existing methods (10,11).…”
Section: Methodsmentioning
confidence: 99%
“…In general, MPs showed no surface-deposited drug crystals and a rough uneven surface with deep grooves. Surface characteristics of MPs are the result of the interplay of preparation conditions including the emulsification method (35) and solvent type (36). Differences in morphological characteristics of MPs made of Eudragit RS100 and L100 could be attributed to differences in viscosity and solvent evaporation rate from their respective solutions in addition to potential interaction of the anionic Eudragit L100 with VRP (37).…”
Section: Morphology Of Vrp Mpsmentioning
confidence: 98%